BL_GERICHTE 730 16 273/137 vom 24. Mai 2017 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht, vom 24. Mai 2017 (730 16 273/137) - BL Gerichte (2017)
Leistungen/Rechtsverweigerung